(untitled) (New York, 2015)
Essentials of Sociology moves students beyond their individual experiences by highlighting the macro social forces at work in our everyday lives. New “Digital Life” features in the Fifth Edition encourage students to think critically about how the Internet and smartphones are transforming the way we date, manage our health, and even practice religion. Innovative pedagogy, including end-of-chapter concept maps and a goal-focused organization, help students master the core concepts and see the big picture.
Keywords: Xã hội học,Sociology